Fundamental Models of Consumer Purchasing Behavior - Hasnaa El gozmir; Samir Makhrout; Abderrahmane Chouhbi (Revistamultidisciplinar.com, 2024)
This paper explores established models of the consumer decision-making process, originated from the 1960s, and assesses the viewpoints of Nicosia, Howard and Sheth, Engel, Kollat and Blackwell, and Fishbein and Ajzen's theories of reasoned and planned behavior. Subsequently, it demonstrates their significance and linkages with current marketing practices, encompassing the effects associated with digitalization and the augmentation of consumer requirements. Finally, the paper puts forth a theoretical model for the decision-making process. These models provide diverse perspectives on how consumer attitudes, purchasing decisions, and interactions with marketing stimuli are formed. However, it is emphasized that these models must continually evolve to remain relevant in an ever-changing environment, as they are critical in comprehending consumer behavior and developing marketing strategies.